The Effectiveness of STEAM (Science, Technology, Engineering, Art, and Math) to Improve Students' Achievement in Electrochemistry - Sheila Wanni Lubis, Ervi Luthfi; Rahmania, Sri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research have goals to determine the increase in student learning outcomes using STEAM learning is better than improving student learning outcomes using direct instructions in Electrochemistry Before treatment, 25 pretest questions were given . Then given a different treatment, the experimental class studied using STEAM learning and the control class studied with direct instructions. After the treatment given a post-test. In the pretest, the experimental class average was 40.11 and in the control class was 39.11. In the post-test, the experimental class was 83 and the control class was 75.40. The effectiveness of STEAM learning is 25% compared to Direct Instructions. The conclusion of this research is learning outcomes using STEAM learning are better than Direct Instructions. The difference in student learning outcomes using STEAM with student learning outcomes using the lecture method is 19%.